2007
DOI: 10.1152/jn.00707.2006
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Models for Radial Distance Determination by the Rat Vibrissal System

Abstract: Rats use active, rhythmic movements of their whiskers to acquire tactile information about three-dimensional object features. There are no receptors along the length of the whisker; therefore all tactile information must be mechanically transduced back to receptors at the whisker base. This raises the question: how might the rat determine the radial contact position of an object along the whisker? We developed two complementary biomechanical models that show that the rat could determine radial object distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
230
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(237 citation statements)
references
References 31 publications
7
230
0
Order By: Relevance
“…This technique is inspired by the apparent use of a gestalt-like approach by hunting shrews [12] but also likely reflects a more general approach to perception in biological systems [31]. Whilst the model we have developed assumes contact occurs at the tip of the whisker, the extension to contact along the shaft is straightforward provided the contact location can be estimated, and this certainly appears to be possible [44,45]. The extension to many percepts in this case is also straightforward both algorithmically and computationally, since each percept is treated as independent.…”
Section: Reviewmentioning
confidence: 99%
“…This technique is inspired by the apparent use of a gestalt-like approach by hunting shrews [12] but also likely reflects a more general approach to perception in biological systems [31]. Whilst the model we have developed assumes contact occurs at the tip of the whisker, the extension to contact along the shaft is straightforward provided the contact location can be estimated, and this certainly appears to be possible [44,45]. The extension to many percepts in this case is also straightforward both algorithmically and computationally, since each percept is treated as independent.…”
Section: Reviewmentioning
confidence: 99%
“…When a vibrissa touches an object, reaction forces and bending moments are generated at the vibrissa base (Kaneko et al, 1998;Solomon and Hartmann, 2006;Birdwell et al, 2007;O'Connor et al, 2010;Quist and Hartmann, 2012). These mechanical signals are transduced to electrical activity by mechanoreceptors within a densely innervated follicle (Ebara et al, 2002;Lottem and Azouz, 2011), and the activity from many mechanoreceptors is then integrated by primary sensory neurons of the trigeminal ganglion, Vg (Szwed et al, 2003(Szwed et al, , 2006Jones et al, 2004;Leiser and Moxon, 2007;Khatri et al, 2009;Lottem and Azouz, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have developed quasi-static models that relate the bending of the vibrissa to the forces and moments at the vibrissal base Hartmann, 2006, 2011;Birdwell et al, 2007;Quist and Hartmann, 2012). Other studies have developed models of vibrissal resonance (Hartmann et al, 2003;Neimark et al, 2003;Boubenec et al, 2013;Yan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…First, using biomechanical modeling and data obtained using plucked rat whiskers, Birdwell et al [6] have shown that the radial distance to a point of contact can, in principle, be calculated by measuring the rate of change of moment (or equivalently curvature) at the whisker base. Further, this method has been shown to be useful for recovering distance information in an artificial vibrissal sensing system using steel-wire whiskers, gauged for strain, and fitted to a columnar whisking apparatus exploring a complex three-dimensional shape [36].…”
Section: Discussionmentioning
confidence: 99%